The impact of selected variables on the VAT gap in the Member States of the European Union - Ingrid Majerová (Institute of Economic Research (IER), 2015)
One of the most serious problems of fiscal character is the issue of the tax gap. The tax gap is defined as the amount of tax liability faced by taxpayers that is not paid on time. The tax gap comes from three main areas of non-compliance with the tax law - firstly from underreporting of income, secondly from underpayment of taxes and thirdly from non-filling of returns. The tax evasions in the area of value added tax form one of the largest groups of tax gap. This article describes the current situation in the field of tax gap in selected countries of the European Union, namely the VAT gap. The aim of this paper is to determine a dependence of the VAT gap on three variables, the Corruption Perception Index CPI, GDP growth rate and the basic VAT rate. A method of the regression analysis has been used, performed on data in the years 2000-2011. In spite of the fact that it could be assumed that tax burden will affect the VAT gap the most, the highest dependence was shown in the case of the Corruption Perception Index.
Keywords: H26; H32; 330; tax gap; value added tax; Corruption Perception Index; GDP growth; VTTL model; regression